Circulating saints: a study of the movement of corporeal relics in three regions of Western Europe, c. 800-1200 - Wiedenheft, Elizabeth Anne (2018)
This thesis is concerned with the movement of corporeal relics in France, England and the Low Countries during the central Middle Ages. There were two types of relic movements in medieval Europe. The first of these forms a broad category termed translationes, and includes the theft of relics (furta sacra) as well as intra-site translations (the movement of relics within a specific site) and regional translations (the movement of relics from one site to another). The second type of relic movement was the delatio, or the tour of relics. Communities were motivated to move their relics by numerous factors, including protection from harm or theft, to claim land, to provide protection to a specific area (including from war or pestilence), or to build wealth or focus a community around a specific secular or religious identity. The latter often meant that the movement of relics was performed as part of a deliberate relic policy of the leaders of that community, and helped to promote a common identity, thus binding the people of that area together as a social group. They also could be used to build boundaries around lands that were either desired by or owned by a particular monastic community, thereby allowing the monastery to acquire new lands and endowments.